Enhancing Service Delivery through an Online Complaints System for Northern Ghana’s Tertiary Institutions - Ali, Mumuni; Azaare, Jacob; Zhao, Wu; Engmann, Gideon Mensah (Universitas Bina Darma, 2024)
This study investigated the factors hindering the successful implementation of online complaints system in tertiary institutions in Northern Ghana, and developed an effective complaint system to enhance service delivery, using iterative waterfall models with CSS, MYSQL, JavaScript, HTML, and visual studio codes. To identify the factors hindering the successful implementation of online complaints system, a structured questionnaire was administered to a sample of 308 participants to ascertain the factors that influence the implementation of online complaints system. The findings revealed that lack of education and training, and inadequate resources are the key factors hindering the implementation of online complaint system. Consequently, a new complaint system was developed from this study which incorporated speech-to-text, and text-to-speech features to cater for the needs of diverse users, unlike the previous ones. This new complaint system was found to be cost effective since students only need access to internet connectivity to lodge complaints, unlike previous ones where students have to travel to school before lodging complaint. Finally, the new complaint system equally efficiently handles students’ complaints by keeping a record of all previously lodged complaints of the user, this particular feature provides educational institutions with insights on the frequency of complaints lodged by users. Based on the results, it is evident that tertiary institutions which are looking forward to adopting and implementing students’ complaints system, should consider educating and training for both staff and students on its usefulness. Also, tertiary institutions are encouraged to adopt and implement this system since it is less frustrating and cost effective.